An open QoS architecture for CORBA applications. - CAHILL, VINNY (IEEE Computer Society, 2000)
Distributed application programmers rely on middleware such as CORBA in order to handle the complexity that arises from the distributed and heterogeneous nature of the underlying computing platform. CORBA, in particular, provides a media streaming mechanism that can be used for media streaming and for associating QoS requirements with media streams. Despite defining the interfaces of the media streaming mechanism, the corresponding specification does not prescribe how QoS is enforced at low-level by the middleware. This paper describes the design and implementation of a QoS architecture, called Quartz, which has been integrated with CORBA in order to provide a framework that allows applications to transfer real-time media in open systems. This framework is employed to model and simulate a pattern recognition mechanism for use in an automated manufacturing cell, which is also described and analysed in this paper.
Proceedings of the 3rd International Symposium on Object-Oriented Real-time Distributed Computing (ISORC 2000),
3rd International Symposium on Object-Oriented Real-time Distributed Computing (ISORC 2000),
PUBLISHED
Keywords: Computer Science